Implementation of Electronic Document Management to Support World-class University: A Case Study in Airlangga University - Srirahayu, O D P (KnE Social Sciences, 2018)
In digital age, information technology and the Internet network is no stranger in the community. Almost all the activities in the community of economic activities, education, government to leisure activities, carried out with the involvement of information technology and the Internet. The existence of information technology and the Internet to make someone get in touch with others without being obstructed by time and distance, so a person can communicate and get information effectively and efficiently, therefore many government agencies, educational and private use of information technology and the Internet because it was considered to be help improve the performance and productivity of the company. According to Kang (1998), the information technology system will help the company if the company uses real-time information technology systems and efficient. In college, internet technology used to provide satisfactory service for students and other academics. One embodiment of an effort to provide satisfactory service is the holding of Electronic Document Management (EDM). Keywords: Electronic Document Management System, EDMS, e-office, Mailing